Bibliografija per pirmąjį Tarybų valdžios Lietuvoje dešimtmetį (1940–1950 m.) - Basiulis, Jonas (Knygotyra, 1970)
Under the bourgeois regime in Lithuania the condition of bibliography was very grave. The state paid no attention to that. Only individuals concerned themselves with bibliography. More often than not they were engaged in this work by chance. In 1940, on restoring Soviet power in Lithuania the whole cultural construction, including bibliography, was taken under the care of the state. Satisfactory conditions for the development of bibliography were created at that time. In the bibliographical work one could sense an unprecedented rise, and see great plans made for the future. When studying the development of bibliography in the first decade of Soviet power in Lithuania two periods should be distinguished: (1) 1940–1941 and (2) post-war years. In the course of the ten months of the 1940–1941 period some vast work could not be done. Short as this period was, the bibliographical work was enriched with new problems and plans. The second period. the post-war years. was the time when great plans and projects were put into practice. In 1940–1941, much attention was paid to the state recording bibliography, to establishing the Book Chamber, to compiling a union catalogue of the major libraries in the Lithuanian S.S.R., to organizing centralized cataloguing and training highly skilled bibliographers. Thus, at that time the essential and vital problems of the Lithuanian bibliography were being solved. In bourgeois Lithuania such subjects were of no concern to the ruling classes. Unfortunately, the plans could not be realized as the war burst out and Lithuania was occupied by nazi Germany. On liberating Lithuania from the fascist occupation the measures were taken for establishing the Book Chamber of the Lithuanian S. S. R. and running the recording bibliography. The Book Chamber was founded on the 29th of March, 1945, and that day it was alloted a deposit copy. In 1947, the state recording bibliography organs began to appear: the quarterly „Book Annals“ and the monthly „Annals of Magazine and Newspaper Articles“. In 1946, centralized cataloguing was tackled. The paper deals with the Book Chamber organisation history and describes the beginning of its activities. The work is based on a number of documentary materials. In 1949, „The Annals of Periodical Publications“ made its apparition. Side by side with the recording bibliography the activities of the Book Chamber in the field of retrospective bibliography are considered. The first work of a retrospective character was edited in 1949, and it covered books published in 1946. In the post-war period the recommendatory bibliography gained civic rights. Its first editions appeared in 1948. The paper sets forth the origination and formation of scientific, informative, critical and other modes of bibliography. In 1949–1950, Vilnius State University started training highly skilled bibliographers in its Chair of Library Science. The conference of scientific libraries in the Lithuanian S.S.R. that took place in 1949 held particular promise for future progress of the bibliographical work. There great attention was paid to bibliographical problems. The conference reviewed the development of bibliography, revealed drawbacks and determined the ways of its subsequent growth. The paper makes a conclusion that during the first decade after restoration of Soviet power in Lithuania all basic modes of bibliography were completely formed. Bibliographical work being under the control of the state, the establishment of the Book Chamber, the training of highly skilled personnel, the introduction of bibliography into the library work and other factors played a leading role in developing the bibliography in Lithuania.